The Ends of Philosophy of Religion - Knepper, T. author. aut Link
XIV, 206 p.
Keywords: Knepper criticizes existing efforts in the philosophy of religion for being out of step with, and therefore useless to, the academic study of religion, then forwards a new program for philosophy of religion that is in step with, and therefore useful to, the academic study of religion.